Negotiating Women's Rights in Jordanian Electoral Law: Are they fulfilled? - Saif Ziad Aljunidi; Farah Alshanik; Emad M. Alamaren (Faculty of Law, University of Muhammadiyah Malang, 2025)
The research analyses legal guarantees for politically empowering women from a comparative perspective and the factors that limit their effectiveness. The research findings show that the sustainability of women’s representation in Jordan’s Parliament depends heavily on the force of law. Women’s representation in Parliament is a temporary measure and is practically considered an alternative to competitive integration. Although those measures contributed to women's representation rising to 19.6% of the House of Representatives’ seats and went beyond formal (token) representation, the percentage remained below the effective “critical mass” of 30%. From a pluralism governance perspective, the study uncovered a severe weakness in youth representation in Parliament at 4.3%, although they represent 60% of the population. The paper highlights the socio-political challenges surrounding the effectiveness of women's empowerment legal guarantees, which are tribal elections, discriminatory practices, and electoral violence against women in the digital space. To handle those gaps, the research recommends legislative reformations such as redividing political districts, reengineering the quota system, adopting a gender alternation system (zipper system), modifying the financial support for the party-based level, while linking it to the percentage of women’s representation beyond the quota, and fostering transformation that supports women’s political participation.